A single-center real-life study on the use of medical cannabis in patients with dystonia - Anis, Saar; Faust-Socher, Achinoam; Sverdlov, Diana; Lassman, Simon; Hezi, Neomi; Anis, Omer; Leor, Gil; Korczyn, Amos D.; Giladi, Nir; Gurevich, Tanya (Frontiers in Neurology, 2023)
Background While cannabis-based medicine is being commonly used in patients with movement disorders, there is a scarcity of publications regarding the effect of cannabis on dystonia. We aimed to describe medical cannabis use in patients with dystonia and related pain. Methods We employed a structured interview to obtain data on the cannabis treatment regimen, perception of effectiveness and side effect profile. Eligible participants were patients diagnosed with dystonia from the movement disorders unit at the Tel-Aviv Medical Center who had used licensed medical cannabis between January 2019 and January 2021. Results Twenty-three subjects were interviewed (11 women, mean age 52.7). The most common way of administration was smoking (n = 11). Following an average of 2.5 ± 2.9 years of use, those with widespread dystonia (generalized, hemi and multifocal, n = 11) self-reported on a numeric rating scale an average 63% (range 0%–100%) reduction in symptoms of dystonia, while those with more focal dystonia patterns reported a significantly lower treatment effect of 32%. Participants reported a positive impact in related pain and quality of life, with an average rating of 3.8 out of 5 (SD = 1.2, median = 4) and 3.6 out of 5 (SD = 1.15, median = 4), respectively. Most common side effects were dry mouth (65%), sedation (43%), dizziness (39%) and psychiatric disorders (26%). Three patients (13%) discontinued therapy. Conclusion A subset of dystonia patients who use medical cannabis under clinical observation reported significant subjective improvement during 30 months of use in average. Further prospective randomized controlled trials are required to examine the effectiveness of cannabis in dystonia.